Diagnosis of heparin-induced delayed type hypersensitivity - Schindewolf, M.; Ludwig, R. J.; Wolter, M.; Hardt, K.; Kaufmann, R.; Lindhoff-Last, E.; Boehncke, W.-H.; Kahle, B. (Phlebologie, 2010)
Heparin is commonly used for prevention and therapy of thromboembolic diseases. Recently, work from a prospective epidemiological investigation has indicated, that heparin-induced skin lesions may be more frequent, than expected. Commonly, delayed-type hypersensitivity reactions can be identified as the cause of heparin-induced skin lesions. Rarely, immediatetype hypersensitivity responses or immune-mediated heparin-induced thrombocytopenia (HIT) are diagnosed. It is of clinical importance to differentiate between those, as patient management is fundamentally different. Patients, methods: We evaluated diagnostic procedures used to identify causes of heparin-induced skin lesions. Based on clinical presentation, histology and/or allergologic testing in 32 patients, heparin-induced delayed-type hypersensitivity (HIHS) was diagnosed. Results: Sensitivity of histology and s.c. provocation was high, amounting to 100% or 78% respectively. All other tests were unspecific or had a low sensitivity: Immediate readings of prick tests were false negative in 81%. Patch, prick and i.c. testing had a sensitivity ranging from 3.1–15.6%. Conclusion: Based on these results and despite the limitations of histology we recommend performing a skin biopsy rather than allergologic testing for diagnosis of HIHS. Compared to allergologic testing, results from histology are sensitive, readily available and may allow a differentiation from other causes of heparin-induced skin lesions.
Keywords: Heparin; type IV allergic reaction; heparin-induced thrombocytopenia type II; adverse event; allergy; delayed type hypersensitivity